Revitalizing the Study of Nusantara Manuscripts through the Ngariksa Program: Oman Fathurrahman’s Contribution to the Development of Digital Philology - Muhamad Yusuf Sidiq (Journal of Islamic History and Manuscript, 2025)
This study examines the contributions of Oman Fathurrahman in revitalizing the study of Nusantara manuscripts through the Ngariksa Program (Ngaji Manuskrip Kuno Nusantara), which integrates traditional philological approaches with modern digital technology. As a professor of philology at UIN Syarif Hidayatullah Jakarta, Oman Fathurrahman has played a pivotal role in the digital transformation of Nusantara manuscripts by developing and leading the Ngariksa Program since 2019. This program is broadcast live on social media and has garnered significant attention from academics and younger generations. It successfully encourages the preservation and study of ancient manuscripts as a valuable cultural memory of the nation. Additionally, Oman actively participates in digitization and cataloging initiatives such as DREAMSEA and the Endangered Archives Programme, expanding global access and utilization of Nusantara manuscripts. This study highlights Oman's strategy of strengthening research infrastructure, digital manuscript utilization, and big data management to advance digital philology as an intellectual heritage of the nation while safeguarding the preservation of manuscripts against modern threats. The findings illustrate that revitalizing Nusantara manuscript studies is not merely an academic endeavor but a vibrant cultural movement involving cross-generational collaboration and digital technology